SOCIALIZATION OF ADAPTATION AND NEW HABITS AFTER THE COVID-19 PANDEMIC AT THE HOSPITAL. ABDOEL WAHAB SJAHRANIE (Jurnal Abdimas Administrasi Kesehatan, 2021)
After the COVID-19 pandemic, we have succeeded in changing the habits we do every day both at home, at school, at work, on the street, in the right worship and everywhere. New habits after the COVID-19 pandemic to live healthier must be continuously carried out in society and every individual, so that it becomes a social norm and a new individual norm in everyday life. Various responses and reactions are shown by health workers to change people's attitudes and behaviors. Thus the relationship between interacting individuals is always a mutually influencing (reciprocal) relationship. An alternative problem-solving framework is carried out by socializing adaptation and new habits after the COVID-19 pandemic at Abdoel Wahab Sjahranie Hospital.  The purpose of this socialization is health promotion from both the community and health workers at Abdoel Wahab Sjahranie Regional Hospital. The adaptation of new habits during this pandemic is not without purpose. The implementation of community service activities is carried out from December 1-3, 2020. On socialization carried out at the hospital. A. W. Sjahranie on December 1, 2020, was attended by 20 participants of health workers. Then, on December 2, 2020, it was attended by 50 community participants. Finally, on December 3, 2020, attended by 80 community participants. So that the total peseta of community service activities for the undergraduate health administration study program is about socializing adaptation and new habits after the COVID-19 pandemic at the Hospital. A. W. Sjahranie had 150 participants. Socialization of hospital accreditation to health students and hospital staff to community participants and health workers is proven by directly 100% categorized as good